Ethics in the university: the horizon of Agenda 2030 and Integral Ecology - Martínez Martínez, Julio Luis (Razón y fe, 2019)
This year marks the 25th anniversary of the implementation of the subject of professional ethics in the respective academic programs of the Universidad Pontificia Comillas and other centers of UNIJES (Jesuit Universities of Spain). The UNIJES centers conceive the ethical formation of students as an important part of the identity of their educational style, oriented towards professional practice and commitment to the construction of a more humane society; and they have a valuable collection of 17 professional ethics manuals on different career fields, written by their professors. Throughout these five decades, the understanding of ethics has been profoundly transformed by globalization and the technological and digital revolution, and the world today has orientation frameworks such as Agenda 2030 and the “integral ecology” of Laudato si´, both of high value to the University.
Keywords: Ethics; university; Agenda 2030; Laudato si´; integral ecology